Ixodid ticks of Western Palearctic bats: ecology, host-parasite relationships, geographic distribution and zoonotic importance - Sándor, Attila D.; Domșa, Cristian; Péter, Áron; Hornok, Sándor (Frontiers in Veterinary Science, 2025)
Bats in the Western Palearctic are host for diverse array of ectoparasites, including three ixodid ticks (Ixodes ariadnae, I. simplex, and I. vespertilionis), which are highly specialized to parasitize these mammals. In this study we collected and analyzed 3,965 host-tick records across 31 bat species from published literature, online sources, and unpublished field data. Individual bat-specialist ticks showed distinct host preferences, with cave-dwelling bats accounting for over 90% of all records. Ixodes vespertilionis was the most generalist of them, with a broad host range and distribution, while I. simplex was highly host-specific, primarily parasitizing a single host species, Miniopterus schreibersii. Ixodes ariadnae had a similar host spectrum as I. vespertilionis but more restricted geographical range, likely influenced by seasonal and life history factors. Our findings revealed substantial geographical overlap in tick distributions across Central and Eastern Europe. Free-living tick stages were predominantly found in caves, and males were observed more frequently than females. Non-bat specific, as well generalist ticks such as Ixodes ricinus and Rhipicephalus sanguineus s.l. were rare on bats, with larger bat species being the more common hosts. These ticks may host DNA of several bacterial, viral, and parasitic pathogens, suggesting an important role in pathogen transmission to bats and possibly other mammals. This study underscores the ecological significance of bat-specialist ticks and highlights the need for further research on their distribution, host interactions, and role in zoonotic disease transmission.